Key factors determining indoor air PM10 concentrations in naturally ventilated primary schools in Belgrade, Serbia - Matic Branislava; Rakic Uros; Jovanovic Verica; Dejanovic Snezana; Djonovic Nela (Sciendo, 2017)
Indoor air quality (IAQ) is rated as a serious public health issue. Knowing children are accounted as more vulnerable to environmental health hazards, data are needed on air quality in schools.